2018
DOI: 10.21003/ea.v170-05
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise management in VUCA conditions

Abstract: Enterprise management in VUCA conditions Abstract. Today's world, which is characterised by variability, uncertainty, complexity and ambiguity (VUCA), poses a problem associated with a shift in the business administration paradigm. Therefore, the purpose of this paper is to define the features and develop a conceptual model of business administration in the VUCA world. The article defines the components of the VUCA world and describes their impact on business administration. The research was conducted from Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
(5 reference statements)
0
17
0
1
Order By: Relevance
“…Furthermore, the management and strategic planning elements work in tandem with information-sharing capabilities and effective information flow in generating a favorable organizational environment, which is critical in managing VUCA in the market setting (Triraharjo et al, 2020) (Rose et al, 2019). Kryvoruchko et al (2018) suggested in their study on enterprise management in a VUCA environment that SMEs must be more dynamic in their entrepreneurial management and more agile in adjusting their business models to remain relevant to evolving customer trends that have become more sophisticated in recent years. This fluidity will ensure that an organization can comprehend and meet consumer demands, thereby acting as a catalyst for businesses to mitigate the influence of VUCA (Hamid, 2019).…”
Section: Organization Performance Factors Inmentioning
confidence: 99%
“…Furthermore, the management and strategic planning elements work in tandem with information-sharing capabilities and effective information flow in generating a favorable organizational environment, which is critical in managing VUCA in the market setting (Triraharjo et al, 2020) (Rose et al, 2019). Kryvoruchko et al (2018) suggested in their study on enterprise management in a VUCA environment that SMEs must be more dynamic in their entrepreneurial management and more agile in adjusting their business models to remain relevant to evolving customer trends that have become more sophisticated in recent years. This fluidity will ensure that an organization can comprehend and meet consumer demands, thereby acting as a catalyst for businesses to mitigate the influence of VUCA (Hamid, 2019).…”
Section: Organization Performance Factors Inmentioning
confidence: 99%
“…This legal aspect (regarding the legal responsibility of a business) is of extreme importance and priority in the VUCA world, especially given the circumstances that indicate the commission of administrative offenses in the financial sector [26][27][28]. T hus, given the formulation of the economic problem, its analysis and specific processes for constructing mathematical models (relevant, accurate, productive and economic) and their application to a real economic object under conditions and in the reality of the VUCA world [1; 16-18], we recommend to present the improved system of indicators for the economic and statistical determination of enterprise efficiency (with regard to the legal aspects of management) in the form of economic and mathematical model (1) [3; 5; 21; 29-32]:…”
Section: скриньковський русланmentioning
confidence: 99%
“…Enterprises, organizations and individuals are consumers of MTC in the market of transport and logistics services for the transportation of goods. Most companies operate under conditions of VUCA (volatility, uncertainty, complexity, ambiguity) [7], which require timely management system transformations and formation of high flexibility of structures and processes. Authors of paper [7] emphasize a necessity to consider broader issues in meeting consumer needs.…”
Section: на основI застосування теорIї нечIтких множин розроблено пIдmentioning
confidence: 99%
“…Most companies operate under conditions of VUCA (volatility, uncertainty, complexity, ambiguity) [7], which require timely management system transformations and formation of high flexibility of structures and processes. Authors of paper [7] emphasize a necessity to consider broader issues in meeting consumer needs. Thus, dynamically changing market conditions and the constant growth of competition in the market of transport and logistics services require continuation of the research in the part of the theoretical substantiation of tools for diagnosing customer loyalty in an uncertain environment.…”
Section: на основI застосування теорIї нечIтких множин розроблено пIдmentioning
confidence: 99%